PEMANFAATAN LAHAN DI BAWAH POHON KELAPA DI DESA PAKUWERU KECA-MATAN TENGA KABUPATEN MINAHASA SELATAN (Utilization of Land Under Coconut Tree in Pakuweru Village, Tenga District, Minahasa Selatan Regency) - Filia I. Kila; O. Esry H. Laoh; Lyndon R. J. Pangemanan (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aimed to identify the types of plants cultivated under coconut trees and to assess the income level of farmers who utilized land under coconut trees in Pakuweru Village, Tenga District. This research was conducted in Pakuweru village, Tenga District and started from April 2021 to June 2021. The data used were primary data through direct interviews and secondary data through the village office. Primary data were collected using questionnaires to 30 respondents who were farmers utilizing land under coconut trees for cultivation. Furthermore, the data were analyzed descriptively.The results showed that the largest income was obtained from corn cultivation, which was Rp. 164,838,145 with an average income of Rp. 10,989,210. While the smallest income generated by eggplant cultivation which was Rp.497,000 with an average income of Rp.497,000.